Sentiment Analysis of Electric Vehicles using the Naïve Bayes Algorithm - Adhitia Erfina; Rita Ajeng Lestari (Sistemasi: Jurnal Sistem Informasi, 2023)
Industrial resolutions that are increasingly developing make many transitions in all fields. The increasing use of fuel for vehicles makes Indonesia's fuel stocks run low. Electric vehicles are one type of vehicle that uses electricity. The presence of electric vehicles is expected to be a solution to save fuel oil. Another advantage of electric vehicles is that electric vehicles produce low emissions so that apart from irritating fuel stocks, air pollution will also be reduced. However, the presence of electric vehicles is still a pro and contra in society. One of the media where people express their opinions is the social media Youtube. Testing was carried out using the K-Fold Cross Validation and the Naïve Bayes algorithm. From this test, an accuracy value of 82% was obtained with the polarity of the sentiment obtained, namely negative sentiment of 82% while positive sentiment of 18%. The purpose of this study is to determine the polarity of sentiment and the accuracy value obtained. It is hoped that this research can be properly conveyed to related parties for future progressKeywords: Electric Vehicle, Nave Bayes, K-Fold Cross Validation